Hubungan Keseimbangan Kehidupan Kerja dan Keterkaitan Pegawai dengan Kepuasan Kerja - Marsela Giovani Aritonang; M Rajab Lubis; Nadra Ideyani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The aimed of this research is to determine the relationship between work life balance and employee engagement with job satisfaction among the employees of PT Bank Central Asia Medan. The problem is focused on the work life balance and employee engagement by the company. Measuring tool use is work life balance scale, employee engagement scale, and job satisfaction scale to 92 employees of PT Bank Central Asia Medan and conducting quantitative data analysis with correlated method. The results obtained that there is a significant positive relationship between work life balance and employee engagement with job satisfaction. With the value of F = 4.16 and the value p = 0.000. Work life balance contributes to job satisfaction of 22%. Employee engagement contributes to job satisfaction  of 16.7%. work life balance  and employee engagement to job satisfaction as much as 38,7% this means there are still 61,3% other factors that can affect Job satisfaction.